Particle energization by a substorm dipolarization. Issue 1 (19th January 2017) - Kabin, K.; Kalugin, G.; Donovan, E.; Spanswick, E.
Abstract: Magnetotail dipolarizations, often associated with substorms, produce significant energetic particle enhancements in the nighttime magnetosphere. In this paper, we apply our recently developed magnetotail dipolarization model to the problem of energizing electrons and ions. Our model is two‐dimensional in the meridional plane and is characterized by the ability to precisely control the location of the transition from the dipole‐like to tail‐like magnetic fields. Both magnetic and electric fields are calculated, self‐consistently, as the transition zone retreats farther into the tail and the area around the Earth occupied by dipole‐like lines increases in size. These fields are used to calculate the motion of electrons and ions and changes in their energies. We consider the energizing effects of the fields restricted to ±15° and ±30° sectors around the midnight meridian, as well the axisymmetric case. Energies of some electrons increase by a factor of 25, which is more than enough to produce observable ionospheric signatures. Electrons are treated using the Guiding Center approximation, while protons and heavier particles generally require description based on the Lorentz equations. Key Points: Model describing the nighttime transition region between dipolar and tail‐like magnetic field lines is presented Tailward propagation of a dipolarization front is analyzed Energization of electrons and ions by tail dipolarizations is studied